2021
DOI: 10.1002/stc.2781
|View full text |Cite
|
Sign up to set email alerts
|

Integrated InSAR monitoring and structural assessment of tunnelling‐induced building deformations

Abstract: Summary Structural deformation monitoring is crucial for the identification of early signs of tunnelling‐induced damage to adjacent structures and for the improvement of current damage assessment procedures. Satellite multi‐temporal interferometric synthetic aperture radar (MT‐InSAR) techniques enable measurement of building displacements over time with millimetre‐scale accuracy. Compared to traditional ground‐based monitoring, MT‐InSAR can yield denser and cheaper building observations, representing a cost‐ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 85 publications
(160 reference statements)
0
10
0
Order By: Relevance
“…The application of MT-InSAR techniques to real case studies and the cross-validation of PS-based results against in-situ measurements have demonstrated the reliability of this approach for health monitoring of different types of assets. Surface deformations can be effectively extracted for individual objects, such as buildings, 30,31,[37][38][39][40]78,79 or linear infrastructure, such as railways, 32,33,80,81 roadways, 56,57,[82][83][84] levees 85,86 and coastal structures. 55 Previous studies have shown the feasibility of these techniques for monitoring the settlement of bridge piers 87 and the structural deformations of bridges.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…The application of MT-InSAR techniques to real case studies and the cross-validation of PS-based results against in-situ measurements have demonstrated the reliability of this approach for health monitoring of different types of assets. Surface deformations can be effectively extracted for individual objects, such as buildings, 30,31,[37][38][39][40]78,79 or linear infrastructure, such as railways, 32,33,80,81 roadways, 56,57,[82][83][84] levees 85,86 and coastal structures. 55 Previous studies have shown the feasibility of these techniques for monitoring the settlement of bridge piers 87 and the structural deformations of bridges.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In more recent work, 33,34,38,[103][104][105][106] InSAR-derived results from different type of structures have been compared with measurements gathered by in-situ instruments and visual inspections, revealing good agreement between the data and enabling the integration of MT-InSAR measurements with damage assessment procedures. 38,39,[107][108][109][110] However, while these studies demonstrate the potential of MT-InSAR for infrastructure monitoring, handling the large amount of PS data for civil engineering applications is still a challenge. A significant part of the postprocessing phase usually takes place using GIS, with the aim of merging the PS data and geospatial databases related to the structures within the monitored area.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations